2009
DOI: 10.1152/jn.90679.2008
|View full text |Cite
|
Sign up to set email alerts
|

Neuromechanics of Muscle Synergies During Cycling

Abstract: . Muscle synergies have been proposed as building blocks that could simplify the construction of motor behaviors. However, the muscles within synergistic groups may have different architectures, mechanical linkages to the skeleton, and biochemical properties, and these put competing demands on the most appropriate way to activate them for different mechanical tasks. This study identifies the extent to which synergistic patterns of muscle activity vary when the mechanical demands on a limb were altered, and add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
99
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(117 citation statements)
references
References 41 publications
13
99
1
1
Order By: Relevance
“…In addition, by using wavelet analysis it is possible to retain both time and frequency information of the EMG signal to evaluate the changes in frequency with respect to muscle excitation duration (von Tscharner, 2000;Wakeling et al, 2002;Wakeling and Rozitis, 2004). In this study we hypothesized that the early derecruitment of slower muscle fibres during muscle relaxation would occur at the highest cycle frequencies, and this would be demonstrated by a relative reduction in the low-frequency component (60-90 Hz) of the EMG intensity at the end of the burst of EMG excitation (Wakeling et al, 2001;Wakeling and Horn, 2009).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, by using wavelet analysis it is possible to retain both time and frequency information of the EMG signal to evaluate the changes in frequency with respect to muscle excitation duration (von Tscharner, 2000;Wakeling et al, 2002;Wakeling and Rozitis, 2004). In this study we hypothesized that the early derecruitment of slower muscle fibres during muscle relaxation would occur at the highest cycle frequencies, and this would be demonstrated by a relative reduction in the low-frequency component (60-90 Hz) of the EMG intensity at the end of the burst of EMG excitation (Wakeling et al, 2001;Wakeling and Horn, 2009).…”
Section: Discussionmentioning
confidence: 94%
“…However, progressive developments in EMG decomposition have made it possible to distinguish faster and slower muscle fibres based on the signal frequency with fast and slow muscle fibres producing high and low EMG frequencies, respectively (Gerdle et al, 1988;Solomonow et al, 1990;Elert et al, 1992;Kupa et al, 1995;von Tscharner, 2000;Wakeling and Rozitis, 2004;Wakeling, 2009;Wakeling and Horn, 2009). In addition, by using wavelet analysis it is possible to retain both time and frequency information of the EMG signal to evaluate the changes in frequency with respect to muscle excitation duration (von Tscharner, 2000;Wakeling et al, 2002;Wakeling and Rozitis, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…EMG signals were preamplified (gain 1000), band-pass filtered (bandwidth 10-500 Hz; Biovision, Wehrheim, Germany) and sampled at 2000 Hz as described elsewhere (e.g. Wakeling and Horn, 2009;Blake and Wakeling, 2014). Electrodes were placed in the mid-region of the muscle belly after the skin had been shaved and cleaned with isopropyl alcohol solution.…”
Section: Muscle Activation Patternsmentioning
confidence: 99%
“…This is the first study to test Hill-type models against in vivo estimates of time-varying muscle forces from human subjects at a range of mechanical conditions. Electromyographic (EMG) recordings from the gastrocnemii of cyclists have shown that the activation patterns of different muscle fibre types vary with cadence (Citterio and Agostoni, 1984;Wakeling et al, 2006;Wakeling and Horn, 2009). However, while muscles are composed of a mix of slow and fast fibres with different physiological and biomechanical properties, Hill-type models are typically composed of a single contractile element with force-length and force-velocity properties that have been estimated from in vitro data collected from single fibres under maximally activated conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation